The California gold rush - Harris, Beatrice (Look at US history., 2022)
Chronicles the history and impact of the California gold rush, and explores how people traveled from all over the country to reach California in hopes of getting rich. Includes color photographs, fact boxes, a timeline, a glossary, and additional resources.